2023
DOI: 10.1111/pce.14754
|View full text |Cite
|
Sign up to set email alerts
|

Extreme drought can deactivate ABA biosynthesis in embolism‐resistant species

Joel A. Mercado‐Reyes,
Talitha Soares Pereira,
Anju Manandhar
et al.

Abstract: The phytohormone abscisic acid (ABA) is synthesised by plants during drought to close stomata and regulate desiccation tolerance pathways. Conifers and some angiosperms with embolism‐resistant xylem show a peaking‐type (p‐type) response in ABA levels, in which ABA levels increase early in drought then decrease as drought progresses, declining to pre‐stressed levels. The mechanism behind this dynamic remains unknown. Here, we sought to characterise the mechanism driving p‐type ABA dynamics in the conifer Callit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…(A) The relationship between stomatal conductance (grey) and foliage ABA level (black) during drought in U. californica , data are generalized additive models (±SE) taken from Mercado-Reyes et al (2023) from the same plants from which gas exchange data was collected. (B-F) The response of stomatal conductance (black dots) to instantaneous branch rehydration (denoted by the vertical line), the foliage ABA level is shown above each panel, the water potential prior to rehydration is shown parallel to the line denoting rehydration, the water potential at the end of the gas exchange trace is also shown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(A) The relationship between stomatal conductance (grey) and foliage ABA level (black) during drought in U. californica , data are generalized additive models (±SE) taken from Mercado-Reyes et al (2023) from the same plants from which gas exchange data was collected. (B-F) The response of stomatal conductance (black dots) to instantaneous branch rehydration (denoted by the vertical line), the foliage ABA level is shown above each panel, the water potential prior to rehydration is shown parallel to the line denoting rehydration, the water potential at the end of the gas exchange trace is also shown.…”
Section: Resultsmentioning
confidence: 99%
“…All data collected to date that reports a peaking-type ABA dynamic during drought has found that this phenomenon only occurs at very low water potentials (less than -4 MPa) and consequently a requirement is highly embolism resistant xylem (Brodribb et al 2014; Nolan et al 2017; Yao et al 2021b; Yao et al 2021a; Mercado-Reyes et al 2023). Recent work in U. californica and C. rhomboidea suggests that ABA biosynthesis is deactivated at water potentials lower than turgor loss point and requires sufficient time for the residual ABA to be conjugated for the levels to decline (Mercado-Reyes et al 2023). Modelling suggests that passive stomatal control in angiosperms is possible once epidermal turgor is lost and the mechanical advantage of the epidermis is removed (Buckley 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single drought stress and combined stress of drought and moderate salt stress resulted in significantly higher root ABA content, while root ABA content under combined stress of drought and severe salt stress was not significantly different from the control. Previous studies have shown that Cupressaceae tree species exhibit p-type ABA dynamics under severe drought, i.e., ABA levels increase early in the drought and decrease as the water potential further decreases ( Brodribb et al., 2014 ; Mercado-Reyes et al., 2023 ). Similar reasons may explain the lower root ABA in DSS group compared with DMS group in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reasons may explain the lower root ABA in DSS group compared with DMS group in our study. Roots are the primary site of ABA synthesis, and the decrease in root ABA content may result from inhibited synthesis under stress ( Mercado-Reyes et al., 2023 ). We observed significantly lower leaf ABA in the DSS group than in the DMS group and hypothesized that p-type ABA dynamics also applied in the leaves of P. orientalis saplings.…”
Section: Discussionmentioning
confidence: 99%